Slaves, Masters, and the Art of Authority in Plautine Comedy - McCarthy, Kathleen, 1962- (Book collections on Project MUSE., 2004)
What pleasures did Plautus' heroic tricksters provide their original audience? How should we understand the compelling mix of rebellion and social conservatism that Plautus offers? Through a close reading of four plays representing the full range of his work (Menaechmi, Casina, Persa, and Captivi), Kathleen McCarthy develops an innovative model of Plautine comedy and its social effects. She concentrates on how the plays are shaped by the interaction of two comic modes: the socially conservative mode of naturalism and the potentially subversive mode of farce. It is precisely this balance of the.